Evaluation Standard for Interior Noise and Stability Detection and Rectification of Operating Trains - HU Jiaqi (Chengshi guidao jiaotong yanjiu)
［Objective］ The interior noise and running stability of operating trains have a direct impact on passenger riding comfort. At present, there is a lack of unified evaluation standards for interior noise and stability of operating trains at home and abroad. It is necessary to study the corresponding detection system and evaluation standards. ［Method］ Aiming at the problems such as high interior noise, poor comfort and car shaking, Shanghai Rail Transit develops an interior noise and stability detection system for operating trains.The application and functional requirements of the system are analyzed, and the system scheme and application scheme are introduced. On this basis, the rectification method and evaluation standard for the interior noise and stability of operating trains are proposed. ［Result & Conclusion］ It is an exploration and practice to carry out a systematic research on the interior noise and stability detection in operating trains. Shanghai Rail Transit has compiled and issued relevant standards for the detection and rectification evaluation of interior noise and stability in operating trains, which not only provide a reference basis for the industry, but also help promoting the formulation of urban rail transit group standards. Combining interior noise, stability indicators and line maintenance operations closely can not only detect potential risks in time, but also significantly improve passenger travel experience.